2023
DOI: 10.1101/2023.04.13.536639
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An integrated single-cell RNA-seq map of human neuroblastoma tumors and preclinical models uncovers divergent mesenchymal-like gene expression programs

Abstract: Neuroblastoma is a common pediatric cancer, where preclinical studies have suggested chemotherapy resistance is driven by a mesenchymal-like gene expression program. However, the poor clinical outcomes imply we need a better understanding of the relationship between patient tumors and preclinical models. Here, we generated single-cell RNA-seq maps of neuroblastoma cell lines, patient-derived xenograft models (PDX), and a genetically engineered mouse model (GEMM). We developed an unsupervised machine learning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…However, other neuroblastoma singlecell studies have raised the question of whether MES cells are bona fide malignant cells. Indeed, a variety of non-malignant cells (Schwann cells, SCPs, fibroblasts, myofibroblasts) that express mesenchymal genes are present in neuroblastoma tumors, making it difficult to discern bona fide MES neuroblastoma cells from non-malignant cells expressing similar gene expression programs 81 . In our analysis, we separated MES and ADRN malignant cells and showed that both populations had the same inferred copy number variation.…”
Section: Malignant Cells In Neuroblastoma Retain Features Of Sympatho...mentioning
confidence: 99%
“…However, other neuroblastoma singlecell studies have raised the question of whether MES cells are bona fide malignant cells. Indeed, a variety of non-malignant cells (Schwann cells, SCPs, fibroblasts, myofibroblasts) that express mesenchymal genes are present in neuroblastoma tumors, making it difficult to discern bona fide MES neuroblastoma cells from non-malignant cells expressing similar gene expression programs 81 . In our analysis, we separated MES and ADRN malignant cells and showed that both populations had the same inferred copy number variation.…”
Section: Malignant Cells In Neuroblastoma Retain Features Of Sympatho...mentioning
confidence: 99%